Allelic diversity of phytoene synthase gene influences the transcription level in citrus fruit among a citrus F(1) hybrid population - Sugiyama, Aiko (Breed Sci, 2017)
Phytoene synthase (PSY) is one of the key regulatory enzyme on the biosynthesis and accumulation of carotenoid in citrus fruits. The transcriptional diversity of PSY is mainly attributed to the structural variation in promoter region among PSY alleles. In aim to clarify how this transcriptional diversity is regulated among them, PSY alleles responsible for carotenoid biosynthesis in the fruits are characterized and their promoter sequences were compared. Based on gene structure and expression pattern of PSY homologues on the clementine mandarin genome sequence, PSY alleles responsible for carotenoid biosynthesis are derived from a single locus in the scaffold 6. AG mapping population possessed four PSY alleles derived from parent lines of A255 and G434, and their F(1) individuals with PSY-g2 allele tended to have low transcription level. From sequence comparison of their promoter regions, the cis-motif alternation from MYBPZM to RAV1AAT might be a candidate to influence the transcription level. Among the ancestral pedigree varieties of AG mapping population, the transcription level of PSY correlated with genotypes of MYBPZM and RAV1AAT motifs in the promoter region of PSY alleles, so that homozygous genotype of MYBPZM showed higher transcription level while heterozygous genotype of MYBPZM and RAV1AAT showed lower transcription level.